Urban Sprawl and Its Impact on land Use and SocioEconomic Condition: A Case Study of Barddhaman District, West Bengal - Dasgupta, Arindam; Paul, Suman (National Geographical Journal of India, 2022)
Urban sprawl is a worldwide phenomenon. It is not only a haphazard physical explosion of urban population but also manifests a disorderly and discontinuous development of urban places. Urban sprawl may also be termed as process which takes place slowly or rapidly to occupy the adjacent land of a city or a town and brings about socio-cultural changes in the land use pattern, demographic features (population growth, literacy rate, occupational structure etc.) and transforms the economic livelihood of the people of the concerned area. In the present study villages within 10 km. circular buffer of Burdwan Municipality have been chosen which are located in Barddhaman - I & II blocks of Barddhaman district, West Bengal. The objectives of the study are two folds- First to identify the direction and type of urban sprawl which has taken place in BarddhamanI and BarddhamanII block during 1971 - 2001 and second, try to assess the nature of influence of this process on the social and economic condition of the study area by selecting three villages within 10 km. circular buffer of Burdwan Municipality. To identify the direction and type of urban sprawl, toposheets, LISS III Images of different time span of the study area have been considered along with different secondary data sources. Village level Census data have been analyzed for four consecutive census years i.e. 1971, 1981, 1991 and 2001 in order to find out the nature of influence of urban sprawl on the socio-economic aspects of the study area. The analysis of satellite imageries of different time span has indicated that the urban sprawl has been spreading fast in the surrounding region of Burdwan Municipality located in both Barddhaman-I and Barddhaman block-II and specially toward eastern direction where urban sprawl has taken shape of ribbon development along the NH -2 . Another type of sprawl i.e., leapfrog development have been found in the north-eastern part of the both the blocks and low density sprawl have been identified in the surrounding region of Burdwan Municipality. The temporal study (2001-2011) of land use of the three selected villages has revealed interesting nature of changes and household survey have portrayed socio-economic characteristics related to sprawl.